Design thinking : the handbook - Uebernickel, Falk... [etall] (Singapore WS Professional, 2020)
Design thinking is more than just a new, one-off method of innovation. Its focus is on establishing an innovation-friendly climate in companies and organizations for the long-term. To achieve this, an interdisciplinary team of authors has composed this 'recipe book' that can be practically applied to your everyday business life. This book is for all who intend to understand and practice the design thinking method in the most rapid and uncomplicated way.The first part describes in depth what this method is all about. The second part of this comprehensive book offers you a step-by-step guide to practically apply design thinking. The subsequent sample cases show how to put theory into practice.
Keywords: Management-Technological innovations; Project management